Perceptions of the impact of depression and anxiety and the medication for these conditions on safety in the workplace. Issue 8 (26th July 2005) - Haslam, C; Atkinson, S; Brown, S; Haslam, R A
Abstract : Background: The number of people taking prescribed medication for anxiety and depression has increased greatly, but little is known of how this medication impacts on safety at work. Aims: To examine the relation between anxiety and depression, prescribed medication, performance, and safety in the workplace. Methods: The research involved nine focus groups with sufferers of anxiety and depression to investigate experiences of mental health problems and the impact of psychotropic drugs. A further three focus groups were conducted with staff in human resources, personnel, occupational health, and health and safety departments, to explore organisational perspectives. The sample comprised 74 individuals drawn from a wide range of occupational sectors. Finally, the results were presented to a panel of experts from occupational medicine, general practice, psychology, health and safety, and psychiatry, to consider the implications for practice. Results: Workers reported that both the symptoms and the medication impaired work performance. Participants described accidents which they attributed to their condition or to the medication. Workers with responsibilities for others, such as teachers, healthcare workers, and managers appeared to present a particular safety risk. Healthcare workers believed that they placed themselves and their patients at risk when carrying out medical procedures. Conclusions: Respondents in this study felt that their symptoms of anxiety and depression and the medication they took to treat these conditions placed them at risk with respect to safety in the workplace. Drawing on the results, the authors outline areas for improvement in the management of mental health problems at work.